Structural Masonry Designers' Manual. - Curtin, W. G. (William George) (John Wiley & Sons, 2008)
This major handbook covers the structural use of brick and blockwork. A major feature is a series of step-by-step design examples of typical elements and buildings. The book has been revised to include updates to the code of practice BS 5628:2000-2 and the 2004 version of Part A of the Building Regulations. New information on sustainability issues, innovation in masonry, health and safety issues and technical developments has been added.